Effects of light intensity on growth, feeding activity and development in common sole (Solea solea L.) larvae in relation to sensory organ ontogeny. (6th November 2014) - Bonvini, Erika; Parma, Luca; Gatta, Pier Paolo; Mandrioli, Luciana; Sirri, Rubina; Martelli, Giovanna; Nannoni, Eleonora; Mordenti, Attilio; Bonaldo, Alessio
Abstract: The effects of four light intensities (1000 lx, 500 lx, 50 lx, 3 lx) on growth, survival and feeding activity in common sole ( Solea solea L.) larvae were studied from 4 to 51 days post hatching (dph). During the pelagic larval stage (4–12 dph), larvae reared at 3 lx showed a lower growth. From 19 onwards, the larvae reared under 3 lx displayed a significant ( P  ≤   0.05) higher SGR than the other treatments and a higher final weight compared to 1000 lx and 500 lx. Survival rate was higher under intermediate light intensities (500 and 50 lx). Larvae reared at 3 lx displayed a significant delay in the degree of metamorphosis compared to the other treatments, while at 33 dph metamorphosis was completed under all treatments. Histological examination revealed the importance of vision and light in the first feeding of this species, while after metamorphosis, the full development of other sensory organs indicated that feeding activity is also mediated by chemosensory perception. Results indicate that high light intensity seems to be more suitable during the pelagic larvae, while the opposite would ensure better growth from the onset of metamorphosis to the benthic phase.